Pantun as Local Cultural Literation Media for Elementary School Students in Indonesia - Yudhi Bagastian; Herlina Usman; Tuti Tarwiyah Adi (Indonesian Journal Of Educational Research and Review, 2023)
Over time, local cultures are forgotten. Many students don’t have interest to their culture. Therefore, the goal of this study is to analyze integration of pantun as local cultural literation media for elementary school students. The research is qualitative and uses the literature study method. This study was carried out by searching journals from the science education journal, ScienceDirect search engine and other keywords pantun, local cultural literacy, media literacy, and poem resulted in 2.855 articles. Derived from ScienceDirect, ERIC, and Indonesian science education. Through above process, ten appropiate articles were obtained. Then analyze, and extracted. This study also uses interview and observation instrument in two elementary schools. The subject of this researches are elementary school’s students and teachers. This study conclude that pantun can be used to improving local cultural literacy students because it is easy to remember, easy to be named, and it can be produced as a branding that can be loaded in banners, posters, flash cards, and other printing media that can be displayed in school corridors, class, gardens, squares, and anywhere that can be adapted to the content of pantun.